Prevalence of Patients With Traumatic Ulcer at RSGM Saraswati Denpasar in 2023 - I Gusti Ngurah Putra Dermawan; Intan Kemala Dewi; Ni Nengah Aderinaarta Pramudani (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: One of the most common soft tissue diseases of the oral cavity is traumatic ulcer. Traumatic ulcer is an ulceration that can occur due to damage to the epithelial tissue of the oral cavity. Locations prone to traumatic ulcers are the mucosal areas of the lips, buccal, and tongue. Traumatic ulcers can occur due to mechanical, chemical, or thermal trauma Material and Methods: This study uses a descriptive observational method with a cross-sectional approach, and the population used were patients who visited RSGM Saraswati Denpasar in 2023. Results and Discussions:. There were 3,874 patients who visited RSGM Saraswati Denpasar in 2023 and 76 patients were found to have traumatic ulcers, resulting in a prevalence of 1.98%. Traumatic ulcers are more common at the age of 20-29 years, 57.89% and more common in women, 65.79%.  Conclusion: From the results of the study, it can be concluded that the age group that more often experiences traumatic ulcers is 20-29 years old, and in the female gender.